Pemanfaatan Olahan Ikan Louhan Merah (Red Devil) Menjadi Nugget Guna Meningkatkan Kesejahteraan Masyarakat Di Desa Sigapiton, Kecamatan Ajibata - Putri Winda Sidabutar; Ewil Wiranda Sitorus; Welmar Olfan Basten Barat (Abdi Jurnal Publikasi, 2024)
Sigapiton is one of the villages in Ajibata District, has an area of ​​72.80 km² (BPS, 2018). Sigapiton Village consists of Hamlet I (Lumban Butar-Butar 1 and Lumban Butar-Butar 2), Hamlet II (Lumban Sirait, Lumban Pea, Lumban Manurung), Hamlet III (Sosor Dolok, Sosor Baringin, Lumban Nauli, Lumban Hasatan). Sigapiton Village has a total of 175 family heads with the assumption that each family has 4-7 people. This is an agricultural sector area such as rice, shallots, corn and the tourism sector. The location of this research was carried out in Sigapiton Village, Ajibata District. The reason for choosing this location was the Community Service Lecture (KPPM) program from the UHKBPNP Water Resources Management Study Program. Empowering women in villages includes development in all aspects of life. Programs planned for village development should directly touch the interests of village communities. Because the community should be involved in the empowerment process. Empowerment through training is not just for honing skills but also as something that can support the economic independence of PKK women/women, empowering the community/PKK women through various means, including: one of them is through PKK women's activities. in processing red lohan fish into nuggets. Red lohan fish is a product that has nutritional value for families, and it is hoped that it can foster interest in entrepreneurship.